IMPROVING CONDUCTOMETRIC QUALITY CONTROL OF STEAM CONDENSATE UNDER THERMAL WATER TREATMENT - Vladimir Nikolayevich Shcherbakov (Вестник Донского государственного технического университета, 2018)
To improve the steam quality control and the process of its generation, to prevent the off-design behavior of the water thermal treatment plants of the TPP, CHPP, and NPP, the techniques and devices for their implementation are developed. They are designed for the operational conductometric quality control of the steam and foam level that is generated on the evaporant water surface at the critical values of its salinity. This permits to improve the accuracy of the measurement results and to use the research work for creating an improved system of the operational control over the steam generation and quality. The system ensures the reduction of the foamover, the improvement of the technical-and-economic indices of the evaporator units and power plants. Long-term testing of the system in an active evaporator will provide numerical results under different operating conditions and draw final conclusions.